THE ENHANCEMENT OF GLASS IONOMER CEMENT HARDNESS BY ADDING GOURAMI SCALES POWDER NANOPARTICLES - Erawati Wulandari; Nadie Fatimatuzzahro; I Dewa Ayu Ratna Dewanti; Anita Faizah (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Material hardness in dentistry is used as a measuring tool to determine the ability of a restoration material to withstand the compressive force of masticatory. The hardness of Glass Ionomer Cement (GIC) is a mechanical property related to the abrasion and compressive strength of the GIC. If the material’s hardness is low, it results in low material resistance and causes a fracture. Therefore, it is necessary to add materials that contain hydroxyapatite (HA), which can increase the hardness of GIC, as in gourami fish scales. Purpose: This research aims to determine the influence of adding Gourami Fish Scale Powder (GFSP) nanoparticles to GIC hardness. Method: The twenty five sample is in tablet form and divided into five sample groups, namely G0: GIC without the addition of GFSP, G1: GIC powder + 0.5% GFSP, G2: GIC powder + 1.5% GFSP, G3: GIC powder + 2.5% GFSP, G4: GIC powder + 3.5% GFSP. Hardness test was using Vickers Hardness Tester. Data were analyzed using a One Way ANOVA test. Result: The average values of the hardness results from lowest to highest were the G0 (55.5 ± 2.70 VHN), G1 (56.9 ± 3.36 VHN), G2 (63.7 ± 7.73 VHN), G3 (66.3 ± 1.44 VHN), and G4 (70.1 ± 4.72 VHN), while the One Way ANOVA test results were significant among all groups (p-value < 0.05). Conclusion: The addition of GFSP nanoparticles increased GIC hardness. The highest hardness value was obtained by adding 3.5% GFSP nanoparticles.